Multiplication Operator on Köthe Spaces: Measure of Non-compactness and Closed Range (2019)
We calculate the measure of non-compactness of the multiplication operator Mu acting on non-atomic Köthe spaces. We show that all bounded below multiplication operators acting on Köthe spaces are surjective and therefore bijective and we give some new characterizations about closedness of the range of Mu acting on Köthe spaces. © 2017, Malaysian Mathematical Sciences Society and Penerbit Universiti Sains Malaysia.